Low-intensity pulsed ultrasound enhances neurite growth in serum-starved human neuroblastoma cells - Ye, Xuanjie; Wang, Zitong; van Bruggen, Rebekah; Li, Xin-Min; Zhang, Yanbo; Chen, Jie (Frontiers in Neuroscience, 2023)
Low-intensity pulsed ultrasound (LIPUS) is a recognized tool for promoting nerve regeneration and repair; however, the intracellular mechanisms of LIPUS stimulation remain underexplored. The present study delves into the effects of varying LIPUS parameters, namely duty cycle, spatial averagetemporal average (SATA) intensity, and ultrasound amplitude, on the therapeutic efficacy using SK-N-SH cells cultured in serum-starved conditions. Four distinct LIPUS settings were employed: A (50 mW/cm², 40%), B (25 mW/cm², 10%), C (50 mW/cm², 20%), and D (25 mW/cm², 10%).Immunochemistry analysis exhibited neurite outgrowth promotion in all LIPUS-treated groups except